2012
DOI: 10.1002/jbm.a.34500
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity study of novel water‐soluble chitosan derivatives applied as membrane material of alginate microcapsules

Abstract: The majority of cell encapsulation systems applied so far are based on polyelectrolyte complexes of alginate and polyvalent metal cations. Although widely used, these systems suffer from the risk of disintegration. This can be partially solved by applying chitosan as additional outer membrane. However, chitosan can be dissolved in water only at a low pH, which limits its use in the field of bioencapsulation. In this study, novel primary and tertiary amine chitosan derivatives have been synthesized, which may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It features excellent biocompatibility and biodegradability alongside ecological safety as well as low toxicity and immunogenicity. CS possesses versatile biological activities and applications, including antimicrobial effect and use as a scaffold in tissue engineering and a carrying system for the delivery of drugs and nucleotides [1721]. Injection of CS solution into the murine knee joint caused a significant increase in the density of newly formed chondrocytes, suggesting that it could facilitate the healing of the cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…It features excellent biocompatibility and biodegradability alongside ecological safety as well as low toxicity and immunogenicity. CS possesses versatile biological activities and applications, including antimicrobial effect and use as a scaffold in tissue engineering and a carrying system for the delivery of drugs and nucleotides [1721]. Injection of CS solution into the murine knee joint caused a significant increase in the density of newly formed chondrocytes, suggesting that it could facilitate the healing of the cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…The data generated for chitosan as an encapsulating hydrogel are limited and chitosan is usually formulated as part of a more complex membrane that also includes alginate or methacrylated glycol [9294] . Also, its application is rather limited because it binds crosslinking molecules at acidic pH and does not bind them at physiological pH [95] . Cellulose was also tested for encapsulation; however, it never reached animal testing [96,97] .…”
Section: B Amentioning
confidence: 99%
“…In vitro studies revealed that chitosan and some of its water soluble derivatives have antifungal activity and may be used for wound healing purposes [5,[8][9][10][11]. According to these findings, we considered in this study 14 low molecular weight WSDC known to be useful for wound healing.…”
Section: Methodsmentioning
confidence: 99%